Research of changes in the level of endothelin-1 in experimental diabetic retinopathy. comparison of methods of correction - Y. Sirman; N. Preis; I. Savytskyi (Kazimierz Wielki University, 2021)
Diabetic retinopathy (DR) according to the WHO is the main cause of decreased vision and blindness due to diabetes. The aim of the study: to compare the effectiveness of correction of vasoconstriction in experimental diabetic retinopathy under the influence of different methods of correction. Our results indicate a violation of the functional state of blood vessels on the 30th day of experimental diabetic retinopathy with subsequent progression of pathological changes on the 60th and 180th day of the study, as evidenced by a significant increase in endothelin-1 in the 2nd group (p <0.001), most pronounced in the 3rd stage.In the analysis of data of group №3 it was found that the correction of pathological conditions with hypoglycemic agents has a positive effect, but does not allow to significantly correct pathologically increased levels of endothelin-1, which indicates the need for additional correction tools other than hyperglycemia.The results of group 4 indicate that the involvement of a donor of nitric oxide and aflibercept in the correction of diabetic retinopathy corrects the level of the studied marker, the most pronounced effect is observed on the 180th day of the experiment, but normative values can not be achieved. It was found that in the 5th group, in which the correction of the simulated pathological condition was performed by reducing hyperglycemia, the introduction of aflibercept and bromfenac gives positive results, but less pronounced than in the 4th group, where L-arginine solution was added to the complex correction. .It was found that rats of group 6, which simulated diabetic retinopathy with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac have a pronounced effectiveness of the proposed method of correction compared to previous methods, the level of vasoconstriction stage and continues to recover in the following stages of the experiment, but does not reach the normative values. The obtained data suggest that the method of correction selected in group 7, which includes reduction of hyperglycemia, administration of aflibercept, solution of L-arginine and citicoline is most effective for normalizing vascular tone and structural and functional state of the endothelium.